A Method to Improve the Accuracy for the Comparison of Consecutively Determined Upper Limb Cross-Sectional Area Profiles of Test Subjects: Impact on (Segmental) Limb Volume and Local Limb Circumference - Houwen, Frans; Stemkens, Johannes; Sonsbeek, Don van; Sonsbeek, Robby van; van der Hulst, René; van Langen, Herman (Lymphatic research and biology, 2025)
Chronic edema management depends on measuring small volume changes over time. Therefore, a highly sensitive, accurate, and reliable technique is needed to objectively judge sequential measurements. The prototype of the Peracutus Aqua Meth (PAM), a new volumetric measuring device, was used in an experimental study. Thirty-nine healthy test subjects were measured three times. The measuring principle of the PAM is based on obtaining a profile of cross-sectional areas along the length of an object or limb. Besides total arm volumes, the volume of any chosen segment can be determined. The utmost tip of the middle finger appeared to be an unreliable reference point. Instead, the concept of "hand median" was introduced to align and compare profiles of cross-sectional areas of sequential measurements. Using the hand median strongly improved the measuring accuracy, rendering standard deviation values of 0.4%-1.3% for (segmental) volume determination. Measurements with the PAM show that accurate local/segmental volume determination of a limb is possible. Standard deviations of less than 1.3% are easily obtained for cross-sectional area and volume determination.